A novel technique for correction of congenital cleft of ala - Kapil S Agrawal; Nilesh K Shende; Nishant Khare; Omkarnath N Deshpande (Wolters Kluwer Medknow Publications, 2014)
Isolated congenital alar defects are extremely rare. In most cases, alar defects are acquired because of burns, trauma, and tumor excisions. We present two cases of congenital alar cleft reconstructed with transposition of ala, conchal cartilage support and use of composite chondrocutanous graft. The described technique attempts to avoid drawbacks of other methods such as rotation flap, and z-plasty technique. Absolute symmetry maintained with no retraction of alar rim on long-term follow-up with good esthetic results.